THE INFLUENCE OF N-RAS GENE MUTATIONS ON THE RESPONSE TO INDUCTION THERAPY IN AML IRAQI PATIENTS (Iraqi Journal of Medical Sciences, 2016)
Background:N-RAS mutations are the most commonly detected molecular abnormalities in hematologic malignancies, especially in those of myeloid origin.Objective:Current study aimed to determine the frequency of N-RAS mutation; and its influence on response to induction therapy in patients with acute myelogenous leukemia (AML) in Iraq.Methods: Peripheral blood and bone marrow samples were taken from 58 newly diagnosed AML patients and 30 individuals with reactive bone marrow were selected as a control group. Samples screened for N-RAS gene mutations using nested PCR were followed by mutation sensitive digestion analysis (MSDA).Results:N-RAS mutations at the time of diagnosis were found in 10/58 (17.24%) patients with AML and no mutation in control individuals. Patients with mutant N-RAS showed lower complete remission (CR) than wild type, the difference was not significant (60% vs. 72.92%, P = 0.414).Conclusion:The current results provide clues for activation of RAS-signaling cascade in AML patients, supporting their role in molecular pathogenesis of leukemia. N-RAS mutations show no influence on CR rate in AML patients. Further studies on larger scale to define the prognostic significance of N-RAS mutations are recommended.Keyword: AML, N-RAS mutation, MSDA, complete remission.
Keywords: AML; NRAS mutation; MSDA; complete remission